Peningkatan Kemampuan Pustakawan Sekolah dalam Mengelola Perpustakaan Berbasis Teknologi Digital : Penelitian - Zulfatun Sofiyani; Faisal Fahmi; Meinia Prasyesti Kurniasari; Mega Putri Mahadewi; Arly Maya Berlyanti; Alf Arira Ananta Aysya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The low level of competence of school librarians in Lamongan Regency in managing technology-based libraries is a major obstacle to modernization. The lack of mastery of information and communication technology (ICT) has resulted in slow services, minimal digitization, and suboptimal information systems. This situation is exacerbated by a lack of training and limited infrastructure, making it difficult for school libraries to remain relevant to the needs of the current generation. The purpose of this study was to improve the ICT competency of librarians in managing digital technology-based school libraries using Inlislite media. The research methods included preparation, training implementation, evaluation, and follow-up. The research subjects were 50 school librarians from kindergarten, elementary school, and junior high school levels. Data analysis used descriptive and inferential statistical techniques to assess changes in librarians' ICT competencies. The results showed that librarians were able to independently manage digital collections using Inlislite. The conclusion of this study indicates that Inlislite training is effective in improving the competencies of school librarians, especially in mastering automation, collection entry, membership management, and circulation features. These findings confirm that Inlislite is the right medium for modernizing school libraries and is capable of improving the quality of technology-based digital services